Communicative Practices in the Workplace: A Historical Examination of Genre Development - Zachry, Mark (Journal of Technical Writing and Communication, 2000)
Although studies of actual communication practices in the workplace are now commonplace, few historical studies in this area have been completed. Such historical studies are necessary to help researchers understand the often complicated origins of genre conventions in professional discourse. Historical research that draws on contemporary genre theory helps address this void. A genre perspective is particularly valuable for helping researchers trace a given type of document's emergence and evolution. This perspective also provides a way of accounting for the connections between communicative practices and the other activities that occupy the attention of workplace organizations. To illustrate what this perspective brings to historical research in professional communication, I examine the development of communicative practices at a national production company that relied on texts to mediate its organizational activities across geographically dispersed locations.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC91bWdkLWxncjYtcWp1ZS1jamh5